Carvedilol prevents impairment of the counterregulatory response in recurrently hypoglycaemic diabetic rats. Issue 2 (6th February 2021) - Farhat, Rawad; de Santana‐Van Vliet, Eliane; Su, Gong; Neely, Levi; Benally, Thea; Chan, Owen
Abstract: Aim: It has been suggested that repeated activation of the adrenergic system during antecedent episodes of hypoglycaemia contributes to the development of counterregulatory failure. We previously reported that treatment with carvedilol, a non‐specific β‐blocker, prevented the development of counterregulatory failure and improved hypoglycaemia awareness in recurrently hypoglycaemic non‐diabetic rats. The current study investigated whether carvedilol has similar benefits in diabetic rats. Methods: Recurrently hypoglycaemic streptozotocin‐diabetic rats (STZ+RH) were treated with carvedilol for one week prior to undergoing a hypoglycaemic clamp. Hypoglycaemia awareness was evaluated in streptozotocin‐diabetic rats made hypoglycaemia unaware using repeated injections of 2‐deoxyglucose. Results: Compared to hypoglycaemia‐naïve STZ‐diabetic controls, exogenous glucose requirements were more than doubled in the STZ+RH animals and this was associated with a 49% reduction in the epinephrine response to hypoglycaemia. Treating STZ+RH animals with carvedilol improved the epinephrine response to hypoglycaemia. Of note, neither recurrent hypoglycaemia nor carvedilol treatment affected the glucagon response in diabetic animals. Additionally, carvedilol treatment improved the feeding response to insulin‐induced hypoglycaemia in diabetic animals made 'hypoglycaemia unaware' using repeated injections of 2‐deoxyglucose, suggesting the treatment improved awareness of hypoglycaemia as well. Conclusion: Our data suggest that carvedilol may be useful in preventing impairments of the sympathoadrenal response and the development of hypoglycaemia unawareness during recurring episodes of hypoglycaemia in diabetic animals. Abstract : Patients with type 1 diabetes lose the ability to recognize when their blood glucose levels go low, and this is due in part to loss of the sympathoadrenal response. Treatment of diabetic rats with low doses of carvedilol improves the sympathoadrenal response to hypoglycemia and their ability to recognize hypoglycemia.